2013
DOI: 10.1126/scitranslmed.3004952
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA from the Papanicolaou Test to Detect Ovarian and Endometrial Cancers

Abstract: Papanicolaou (Pap) smears have revolutionized the management of patients with cervical cancers by permitting the detection of early, surgically curable tumors and their precursors. In recent years, the traditional Pap smear has been replaced by a liquid-based method, which allows not only cytologic evaluation but also collection of DNA for detection of human papillomavirus, the causative agent of cervical cancer. We reasoned that this routinely collected DNA could be exploited to detect somatic mutations prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
270
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(285 citation statements)
references
References 47 publications
(59 reference statements)
10
270
3
2
Order By: Relevance
“…HGSOC disseminates early and preferentially to the peritoneal cavity, suggesting that cancer cells may be more abundant in peritoneal fluid than in the relatively distant uterine cavity or cervix, as previously attempted by other studies (5,14).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…HGSOC disseminates early and preferentially to the peritoneal cavity, suggesting that cancer cells may be more abundant in peritoneal fluid than in the relatively distant uterine cavity or cervix, as previously attempted by other studies (5,14).…”
mentioning
confidence: 65%
“…"Molecular tagging" of single-stranded DNA decreases the rate of false mutations to less than 1 per 10,000 sequenced nucleotides and has been successfully applied to the detection of mutant cancer DNA in a variety of clinical samples (2)(3)(4)(5)(6). However, this false positive error rate limits the specificity of this method in challenging situations in which ultra-deep sequencing is needed to detect extremely low frequency mutant molecules (e.g., <1/10,000), as is the case of ovarian cancer DNA in Pap smears (5). Because true mutations are indistinguishable from artifacts, compromised specificity leads to lower sensitivity and overall low diagnostic accuracy.…”
mentioning
confidence: 99%
“…Hence, RNF43 and ZNRF3 mutations, by sensitizing cells to Wnts, may also be predictive of response to both PORCN inhibitors and Frizzled antibodies. Mutations in RNF43 are surprisingly common, occurring in 18% to 27% of endometrial cancers, 3% to 5% of pancreatic cancers, 21% ovarian mucinous carcinomas, and 38.5% liver fluke associated cholangiocarcinomas (45)(46)(47)(48). Notably, up to 18% of colorectal cancers have RNF43 mutations, often associated with mismatch repair deficient, microsatellite instability (MSI þ ) cancers (46).…”
Section: Rnf43 and Znrf3 Loss-of-function Mutationsmentioning
confidence: 99%
“…These cancers are notably difficult to detect, rarely caught early, and have a very poor prognosis (Stirling et al, 2005). However, recent findings indicate that ovarian and endometrial cancerous cells can be found in the vagina (Kinde et al, 2013). While pap smears (i.e., brushing the cervix to remove cells) are the standard clinical practice used to detect cervical cancer, findings from microbial studies of the vagina (e.g., Kim et al, 2009) indicate that localized sampling may be inefficient for detecting microbial populations (and presumably rare cancerous cells) dispersed through the vagina.…”
Section: Summary Implications and Future Directionsmentioning
confidence: 99%